COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA PENDULANGAN INTAN PUMPUNG CEMPAKA - Gusti Nur Alisa Rizki Andini; Lusia Astrika (Journal of Politic and Government Studies, 2026)
The Diamond Panning tourism attraction in the Pumpung area, Banjarbaru, has historical and local cultural appeal. However, its development faces several challenges, including limited budget, land constraints, and inadequate supporting facilities. This study examines the patterns of collaboration among stakeholders using a qualitative approach and the Collaborative Governance framework proposed by Ansell and Gash (2008). The results show that collaboration indicators such as face-to-face dialogue, trust-building, commitment, and shared understanding have not functioned optimally. The main obstacles include low community awareness, resource imbalances related to land legality, and the financial dependence of Pokdarwis on the government. Therefore, it is necessary to strengthen legal certainty in land use, increase community participation, enhance the financial independence of Pokdarwis, and optimize the role of the private sector in digital marketing.